The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.1093/cvr/cvz016
|View full text |Cite
|
Sign up to set email alerts
|

Lansoprazole alleviates pressure overload-induced cardiac hypertrophy and heart failure in mice by blocking the activation of β-catenin

Abstract: Aims Proton pump inhibitors (PPIs) are widely used in patients receiving percutaneous coronary intervention to prevent gastric bleeding, but whether PPIs are beneficial for the heart is controversial. Here, we investigated the effects of lansoprazole on cardiac hypertrophy and heart failure, as well as the underlying mechanisms. Methods and results Adult male C57 mice were subjected to transverse aortic constriction (TAC) or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 49 publications
2
21
0
Order By: Relevance
“…Protein concentrations were determined using a BCA Protein Assay Kit (Beyotime, P0010). Western blot was performed as described previously 32, 33. The primary antibodies used are presented in Table S8.…”
Section: Methodsmentioning
confidence: 99%
“…Protein concentrations were determined using a BCA Protein Assay Kit (Beyotime, P0010). Western blot was performed as described previously 32, 33. The primary antibodies used are presented in Table S8.…”
Section: Methodsmentioning
confidence: 99%
“…However, it is unclear whether this deficiency of VCP found in the hypertensive hearts is only an accompanying consequence of the cardiac response caused by pressure overload or is a contributor that mediates the cardiac deteriorations. We selected 5 W TAC to test the effects of VCP on pressure overload-induced heart failure for the following reasons: first, this model is an established and the most common heart failure mouse model that has been widely used to mimic human pressure-overload induced cardiac remodeling and dysfunction [ [31] , [32] , [33] , [34] , [35] ]. Numerous studies have confirmed that TAC could provide a reproducible model of cardiac hypertrophy, inflammatory and fibrotic response, and a gradual time course in the development of heart failure [ [31] , [32] , [33] , [34] , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…We selected 5 W TAC to test the effects of VCP on pressure overload-induced heart failure for the following reasons: first, this model is an established and the most common heart failure mouse model that has been widely used to mimic human pressure-overload induced cardiac remodeling and dysfunction [ [31] , [32] , [33] , [34] , [35] ]. Numerous studies have confirmed that TAC could provide a reproducible model of cardiac hypertrophy, inflammatory and fibrotic response, and a gradual time course in the development of heart failure [ [31] , [32] , [33] , [34] , 36 ]. Secondly, TAC could mimic pressure-overload induced morphological and functional alterations of hypertension but excludes the impacts of other potential factors on the molecular alterations that may exist in other hypertensive models, such as the genetic and environmental effects and drug treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac hypertrophy, a morphological adaptive response of the heart to chronic work overload, is characterized by an increase in cardiomyocyte size, enhanced protein synthesis, and re‐expression of the foetal cardiac gene program. Although cardiac hypertrophy is initially a compensatory mechanism, chronic pathological hypertrophy may be deleterious, as it is associated with an increased risk of heart failure and premature death 1‐3 . Although much progress has been made to understand the molecular mechanism of cardiac hypertrophy over the past few decades, the pathogenesis of this disease is yet to be clarified.…”
Section: Introductionmentioning
confidence: 99%
“…Although cardiac hypertrophy is initially a compensatory mechanism, chronic pathological hypertrophy may be deleterious, as it is associated with an increased risk of heart failure and premature death. [1][2][3] Although much progress has been made to understand the molecular mechanism of cardiac hypertrophy over the past few decades, the pathogenesis of this disease is yet to be clarified.…”
Section: Introductionmentioning
confidence: 99%